Kualitas Pelayanan pada Berbagai Bidang Jasa di Kota Serang melalui Kajian Pustaka - Juhandi Juhandi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
One topic that is often discussed in marketing management is service quality. Service quality is an indicator of the service provided by the service provider to the service recipient. Service quality is also an early indicator of customer satisfaction. The aim of this research is to find out what types of service sectors have been researched in the marketing sector, especially service quality in Serang City. This service quality research method uses qualitative methods originating from journals that have been previously researched with research questions including year of publication, field of service studied, dimensions of service quality used, and research methods. It is hoped that the results of this research can intensify research in Serang City, especially service quality related to marketing management. Considering the limited data available and the breadth of the service quality sector for the size of Serang City.